Answer:
4^3x=4^(4x+4)
Step-by-step explanation:
You can eliminate the first 2 options since those don’t make sense already, and the last option changed 64 to 2^6 which is correct, but when they changed the other side. They should have multiplied 8 to both x and 1 which would have made the whole term 2^(8x+8) and not 2^(8x+1). Left with the third option, 4 to the power of 3 is 64 so the left side makes sense, 4^3x=64^x, on the right side, 4^4 equals 256, so the whole exponent should multiply by 4 so from 256^(x+1) you get 4^4(x+1) giving 4^(4x+4) making the third choice the right answer.
Answer
24/5
Step-by-step explanation:
Answer:
1.47
Step-by-step explanation:
9.76/10=10% = 0.976 round to 0.98
5%=0.97/2 = 0.49
add them = 1.47 tip
Answer:
D. (1, -2)
General Formulas and Concepts:
<u>Pre-Algebra</u>
- Order of Operations: BPEMDAS
- Equality Properties
<u>Algebra I</u>
- Solving systems of equations using substitution/elimination
Step-by-step explanation:
<u>Step 1: Define systems</u>
5x - 2y = 9
3x + 4y = -5
<u>Step 2: Rewrite systems</u>
10x - 4y = 18
3x + 4y = -5
<u>Step 3: Solve for </u><em><u>x</u></em>
- Add to equations together: 13x = 13
- Divide 13 on both sides: x = 1
<u>Step 4: Solve for </u><em><u>y</u></em>
- Define: 3x + 4y = -5
- Substitute in <em>x</em>: 3(1) + 4y = -5
- Multiply: 3 + 4y = -5
- Isolate <em>y </em>term: 4y = -8
- Isolate <em>y</em>: y = -2
And we have our final answer!